Anticipation and Motivation as Predictors of Leisure and Social Enjoyment and Engagement in Young People With Depression Symptoms: Ecological Momentary Assessment Study - Angad Sahni; Ciara McCabe (JMIR Mental Health)
Abstract BackgroundParticipating in leisure and social activities can alleviate depression symptoms, yet effective strategies to enhance enjoyment and maintain long-term engagement remain scarce. Gaining insight into the reward subcomponents that influence daily experiences and drive behavior could uncover novel targets for intervention. ObjectiveThis study examines the role of anticipation and motivation in predicting enjoyment and engagement in leisure activities and socializing among young people, and how these relationships are moderated by depression severity, using intensive longitudinal ecological momentary assessments. MethodsParticipants (N=80; mean age 20, SD 2.3 years) used the Psymate2 smartphone app to report mood, enjoyment, current and anticipated activities, and social company 7 times daily for 6 days. Activity categories were relaxation, exercise, other leisure, work or school, studying, chores, shopping, hygiene, eating or drinking, and traveling, and company categories were partner, friends, family, colleagues, acquaintances, strangers, and nobody. Anticipation (anticipatory pleasure and expectation) and motivation (interest and preference) for upcoming activities were rated on Likert scales. Participants were grouped by depression severity, measured using the Mood and Feelings Questionnaire (MFQ): high (HD, MFQ ≥27, N=42), moderate (MD, MFQ 16‐27, N=16), and low, that is, controls (C, MFQ ≤16, N=22). Totally, 2316 assessments met inclusion criteria. ResultsLeisure activities (relaxation, exercise, and other leisure) and social company (partner, friends, and family) were rated most enjoyable across all groups. Higher depression symptoms were associated with reduced enjoyment of studying (β=−.03; PPPPPPPPPPPPPPPPP ConclusionsThese findings highlight the importance of anticipatory pleasure and intrinsic motivation in shaping young people’s engagement and enjoyment of daily activities. Structured or externally driven contexts may dampen enjoyment—especially among those with depression—underscoring the need for novel interventions targeting anticipation and motivation to enhance sustained participation in rewarding activities, leading to improved well-being in individuals with depression.